Mengatasi Ketergantungan Bahan Bakar Fosil di Indonesia: Menuju Masa Depan yang Berkelanjutan - Aprianto, Dimas; Rudy Laksmono; Fitri Angelia Hartati Sinambela; Sri Murtiana (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Fossil energy technologies, such as coal, oil, and natural gas, have been crucial in meeting Indonesia's energy demands but contribute significantly to greenhouse gas emissions and environmental degradation. This study examines Indonesia’s current energy landscape, the potential for transitioning from fossil fuels to renewable energy, and the role of clean energy technologies in supporting this shift. A qualitative research approach was employed, systematically reviewing recent literature to analyze the challenges and opportunities in Indonesia's energy sector. The findings highlight that while fossil fuels remain a dominant energy source, clean technologies like Carbon Capture and Storage (CCS) and improvements in energy efficiency offer promising solutions to reduce emissions. However, significant barriers remain, including high production costs for renewable energy, lack of infrastructure, and technological limitations. The study also finds that increasing investments in renewable energy and diversifying energy sources are critical to achieving Indonesia's energy security and sustainability goals. In conclusion, Indonesia must prioritize a gradual but firm transition to renewable energy, supported by clear policy frameworks, financial incentives, and international cooperation. A diversified energy mix will not only enhance energy security but also help reduce environmental impacts, aligning Indonesia with global climate goals.